2020
DOI: 10.1096/fj.201901864rr
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA KCNQ1OT1 accelerates fracture healing via modulating miR‐701‐3p/FGFR3 axis

Abstract: Emerging evidence highlights the role of the long noncoding RNA (lncRNA) KCNQ1OT1 in fracture healing. Osteoblast proliferation, migration, and survival are pivotal during this process. In this study, we aimed to improve our understanding of the regulatory role of lncRNA KCNQ1OT1 during osteoblast proliferation, migration, and survival. We searched the gene expression omnibus databases and LncBase Experimental V.2 to identify key microRNAs (miRNAs) targets of KCNQ1OT1. MiR‐701‐3p was selected as a differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…LncRNA KCNQ1OT1 promotes ovarian cancer progression by upregulating CAPN10 expression through sponging of miR-142-5p [26]. Moreover, lncRNA KCNQ1OT1 promotes osteoblast proliferation, migration, and survival by sponging miR-701-3p and upregulating FGFR3 [27]. However, the role of lncRNA KCNQ1OT1 in tumor glycolysis has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA KCNQ1OT1 promotes ovarian cancer progression by upregulating CAPN10 expression through sponging of miR-142-5p [26]. Moreover, lncRNA KCNQ1OT1 promotes osteoblast proliferation, migration, and survival by sponging miR-701-3p and upregulating FGFR3 [27]. However, the role of lncRNA KCNQ1OT1 in tumor glycolysis has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of EIF2AK3 can in turn stimulate phosphorylation of EIF2A, leading to increased ATF4 expression, which plays a central role in osteoblast differentiation [32,33]. Indeed, several studies have previously demonstrated that BMP2 plays a regulatory role in various biological processes [34][35][36]. For example, one group found that a BMP activity gradient is essential for normal dorsoventral patterning during gastrulation [37].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence of lncRNA KCNQ10T1 involvement in osteogenic processes have encouraged Chen and his group [39] to explore the role of this lncRNA during osteoblast migration, proliferation and survival, and, therefore, fracture healing. A study about the activity of lncRNA KCNQ10T1 in MC3T3-E1 cells showed that its knockdown leads to cell proliferation suppression with respect to cells with a normal expression of lncRNA KCNQ10T1.…”
Section: Lncrnas As Positive Regulatorsmentioning
confidence: 99%